The influence of Victoria’s Secret new brand image in generating brand trust, brand prestige, brand love, and brand loyalty - Zakiyah Artanti Ratnadewi; Fitri Aprilianty; Annisa Rahmani Qastharin; Nurfaisa Hidayanti (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
This research aims to identify the influence of Victoria’s Secret’s rebranding of brand loyalty by assessing its brand trust, brand prestige, and brand love. This research was conducted using a quantitative approach through an online survey and descriptive statistics with PLS- SEM to analyze the data. The results show that Victoria's Secret’s rebranding brand image has a positive influence on brand trust, brand prestige, and brand love; brand trust in Victoria’s Secret’s rebranding brand image does not have a positive effect on brand loyalty, and brand prestige and brand love of Victoria’s Secret’s rebranding brand image has a positive effect on brand loyalty.